2012
DOI: 10.25011/cim.v35i5.18705
|View full text |Cite
|
Sign up to set email alerts
|

A practical pressure measuring method for the upper urinary tract during ureteroscopy

Abstract: A practical pressure measuring method for the upper urinary tract during ureteroscopy AbstractPurpose: e purpose of this study was to develop and test a method for measuring pressure in the upper urinary tract during ureteroscopic operations and to evaluate its e cacy and clinical signi cance.Methods: A total of 44 patients, each with a ureteral calculus in the proximal ureteral segment, were enrolled in the study group: 21 patients with an acute and 23 with a chronic obstruction. e ureteroscope was passed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…During endoscopic surgery, when IRP exceeds 40 cm H 2 O, arterial blood flow decreases, insufficient venous pressure occurs, and associated renal oxidative damage increases [32]. In studies on semirigid URS, IRP reported is 68-272 cm H 2 O [33][34][35]. In the literature, after URS and fURS, the AKI markers tend to increase within the first 4-6 h postoperatively and then decrease [22,36].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…During endoscopic surgery, when IRP exceeds 40 cm H 2 O, arterial blood flow decreases, insufficient venous pressure occurs, and associated renal oxidative damage increases [32]. In studies on semirigid URS, IRP reported is 68-272 cm H 2 O [33][34][35]. In the literature, after URS and fURS, the AKI markers tend to increase within the first 4-6 h postoperatively and then decrease [22,36].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Few studies evaluated upper tract pressure using different methods [ 4 , 5 ]. Shafik used 3-Fr ureteric catheter to measure the ureteral pressure via a transducer output recorded on a rectilinear recorder [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the wireless sensing performance. The reported pressure changes induced by hydronephrosis [ 24 ] suggest that a sensing resolution of 10 mmHg or less is likely required to detect a sign of the problem, while this was observed to be ≈30 mmHg with the current proof‐of‐concept and tended to deteriorate as the device was placed in a more conductive medium (artificial urine) and/or with increased D AS . One effective approach to addressing this factor is to raise the Q factor of the stent device.…”
Section: Discussionmentioning
confidence: 99%
“…The internal pressure of a kidney is reported to range, on average, from 10.2 mmHg at a normal condition to 32.5 mmHg with chronic ureteral obstruction and to 74.5 mmHg with acute ureteral obstruction. [ 24 ] Traditionally, kidney pressure was characterized using a methodology known as the Whitaker test. [ 31,33 ] This method combines urodynamics with antegrade pyelography to measure the differential pressure between the renal pelvis region in kidney and the bladder using two pressure transducers separately inserted into these sites percutaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation